Planning the Future of a Disabled Person: Civil Law Solutions? - Monterroso Rosas, Marta (Teisė, 2020)
If the disabled person wants to plan, guarantee and design a patrimonial strategy to safeguard future needs, how does the Law respond? Which are the legal instruments one can resort to in order to anticipate or organize mechanisms able to meet the special requirements of a disabled person? This paper aims to analyse this problem, making a connection with the Rule of Law.